Peningkatan Literasi Teknologi melalui Edukasi Pemanfaatan Jaringan LAN untuk Pengujian Kelayakan Sistem - Dhoni Setyanto (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
The development of information technology demands the availability of reliable, efficient, and secure network infrastructure to support various activities, particularly in the process of developing information systems. One important component that cannot be ignored in technology development is system feasibility testing, where the use of Local Area Networks (LANs) plays an effective supporting tool. Despite their limited coverage, LANs offer several advantages, such as high data transfer speeds, the ability to share resources, and flexibility in system development. However, employees' lack of understanding regarding LAN utilization often presents a barrier to the implementation and testing of system feasibility. This community service activity is designed to improve employees' technological literacy through education on the use of LANs in information system testing. The methods applied include counseling, hands-on training, and interactive discussions to strengthen understanding of basic LAN concepts and their application in test simulations. The results of the activity showed a significant increase in participants' knowledge and skills, particularly in understanding the functions, benefits, and steps for implementing LANs in system feasibility testing. Participants were even able to apply the material learned to simple practices, thereby increasing their confidence in implementing it in the work environment. Thus, education related to the use of LAN not only has an impact on increasing technological literacy, but also contributes to the effectiveness of the implementation of information systems in various work sectors.